Worldview Islam Sebagai Solusi Teoritik Dan Aplikatif Dalam Melihat Dinamika Pemikiran Lembaga Dakwah - Yoga Agus Yulianto; Muhammad Firdaus; H.M. Yakub (CV. ITTC INDONESIA, 2025)
Islamic worldview is a conceptual framework that plays an important role as a theoretical and applicative solution in understanding the dynamics of thinking of da'wah institutions. This article discusses how the Islamic worldview becomes a solid ideological foundation as well as practical guidelines for da'wah institutions in facing various contemporary challenges, such as modernization, secularization, religious pluralism, and information globalization. By using the principles of tawhid, the teachings of the Qur'an and Sunnah, and the values of sharia as the main footing, the Islamic worldview allows the development of adaptive da'wah theories that remain consistent with the essence of religious teachings. In addition, this worldview also directs da'wah communication strategies to be more effective through innovations in methods and media for delivering messages without compromising religious integrity. This study confirms that the application of Islamic worldview not only strengthens the religious identity of da'wah institutions but also increases their relevance and impact in the midst of socio-cultural changes of the people. Therefore, an in-depth understanding of the Islamic worldview is needed to build a new paradigm in the development of da'wah thoughts and practices that are responsive to the needs of the times.